Small-scale continuous granulation equipment (1953)
General view of small-scale continuous granulation equipment used at the U.S. Department of Agriculture's Agricultural Engineering Laboratory.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; Fertilizer industry--Equipment and supplies; United States. Department of Agriculture; Machinery